KNOWLEDGE AND PREVALENCE OF EATING DISORDER AMONG NURSING STUDENTS OF LALITPUR, NEPAL - Subedi, Suraksha; Shah, Sanjeev Kumar; Thapa, Monika; Maharjan, Purna Laxmi; Shrestha, Purna Devi (International Journal of Research -GRANTHAALAYAH, 2018)
Background: Perceived socio cultural pressure to become thin has an important impact on eating disorder during adolescence, but less is known about knowledge and prevalence of eating disorders in Nepal. Adolescents face special problems that are less common during childhood. Several studies indicate that the prevalence of eating disorders has been increased among adolescents. Objectives: The aim of the study was to identify the level of knowledge, and prevalence of eating disorders (ED) among adolescents. Specific objectives: To calculate the BMI of the respondents and to associate the BMI with prevalence of eating disorder. Methods: This was a cross-sectional survey in which adolescent girls were selected through purposive non probability sampling technique. The study was based on self-reported questionnaires including eating attitudes test (EAT-26) and BMI measurement. To analyze the obtained data, to calculate the level of knowledge, prevalence and BMI the chi-square was measured. Results: According to diagnostic criteria of EAT-26, 34 students (27.2%) were at risk of ED and scored above the recommended cut-off point on EAT-26. More than fifty percent (60%) of the students had inadequate knowledge, one third (38.40%) had moderate knowledge and very minimal (1.6%) of the students had adequate knowledge regarding eating disorders. BMI calculation reveled that more than half (54.4%) had a normal BMI, one third (28%) were under weight, 16% were overweight and 1.6% were obese. Conclusions: The above results concluded that there is need to conduct structured teaching programs for improving level of knowledge regarding eating disorders and reduce the risk of eating disorders and its effects.